PERAN WORLD FOOD PROGRAMME (WFP) DALAM MENANGANI KRISIS PANGAN DI KENYA TAHUN 2021 – 2023 - Ryantori, Ryantori; Santhi, Putu Dyah Eka (Moestopo Journal of International Relations (MJIR), 2024)
This study aims to analyse the Role of The World Food Programme (WFP) in handling The Food Crisis in Kenya in 2021-2023. The research method used is a descriptive research method with a qualitative approach, where data collection is done through book sources, journal articles, thesis, annual reports, and also internet sites. This research uses the theory of the Role of International Organizations to explain how the WFP's role in handling the food crisis and explain the results of assistance from the WFP to Kenya. The results of the study explain that WFP as an international organization engaged in food has carried out the three roles of international organizations in providing assistance to the country of Kenya. It can be concluded that the role of WFP in handling the food crisis in Kenya has been maximized because WFP fulfils the three roles of international organizations, namely WFP as an instrument, actor, and arena.